What Kind of Property is "Relationship Property"? - Atkin, W R (Victoria University of Wellington Law Review, 2016)
This article explores the meaning of "property" in the Property (Relationships) Act 1976. The definition of "property" in the Act is a wide one and is fundamental to jurisdiction under the Act. The article surveys the spectrum of legislative definitions of property. Then, with respect to the definition in the 1976 Act and in light of contemporary legislative aims, it is suggested that the meaning of the term should not be shackled by traditional concepts. Some of the leading judgments are examined, including two regarding relationship property from the Supreme Court, and it is found that the courts have already been adventuresome.